The local vantage: How views of local government finance vary across councils - Neil Amin-Smith; Mark Choo; David Phillips; Jennifer Glover; Lauren Lucas; Julia Goldsworthy; Nick Jones (Institute for Fiscal Studies (IFS), 2017)
Local government finance in England in the 2010s can be characterised by two major trends: large (albeit varying) cuts to council budgets; and a shift from centralised redistribution of funding towards a greater emphasis on fiscal incentives for revenue growth, most notably via the introduction and potential extension of the business rates retention scheme (BRRS). It is in this context that this report, jointly written by researchers at the Institute for Fiscal Studies (IFS), the Local Government Information Unit (LGiU) and PwC, looks at how the views of councils' decision-makers relate to the characteristics of the councils they represent or work for. In particular, we focus on views in two key areas: the quality of service provision; and the impact and design of the BRRS. Such an analysis allows us to examine whether perceptions of two key issues differ systematically between areas with different financial, political and socio-economic characteristics.
Keywords: 330